PROBLEMS OF CORPORATE GOVERNANCE AT DOMESTIC ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article discusses the status and development trends of corporate governance at domestic enterprises in comparison with foreign ones, identifies problems and suggests possible ways to improve efficiency. The domestic model of corporate governance is analyzed, the diagnosis of its advantages and disadvantages is carried out, the effectiveness of its use in the national economy is isolated. The corporate governance diagnostics of individual domestic corporations was carried out and the prospects for their further development were determined precisely with an increase in the level of corporate governance efficiency.There is no single, generally accepted model of corporate governance that would be used by all countries. However, there are certain defined principles, standards, basic criteria and provisions. The Ukrainian model of corporate governance, in contrast to countries with developed market economies, was formed mainly artificially - by almost simultaneous corporatization and privatization of a huge number of state-owned enterprises. The process of formation of corporate relations in Ukraine was somewhat different from the world and has already passed three stages. The effectiveness of corporate governance is defined as the result of a combination of four factors: features of national legislation, type of ownership, governing bodies, social pressure. The main problems of modern corporate governance, in our opinion, are: the uncertainty of the external environment, the difficulty in using the domestic model of corporate governance, violations of shareholder rights.The transition to a market economy, rapid processes of restructuring and privatization of certain sectors of the national economy have introduced into economic circulation a rather complex category as "corporate governance", which has become the key to successful management of any business unit. Today, the creation of new corporate enterprises is becoming increasingly popular, which in most cases is manifested in the creation of joint stock companies. The effectiveness of their work directly depends on the qualifications of staff, including management, the ability to make and implement decisions, the right management system and so on. The effectiveness of corporate governance is a crucial factor in the success of any company. The problem of the effectiveness of corporate governance is becoming increasingly important in times of economic and political crises, in the period of outflow of qualified personnel, in periods of stagnation of some and the rise of other sectors of the national economy.Today, corporate governance at Ukrainian enterprises is accompanied by many problems that need to be addressed immediately. The main ones are the lack of a single methodology for assessing the effectiveness of corporate governance, unregulated corporate relations. Therefore, it is necessary to develop a method of corporate governance that would take into account all the problems and peculiarities of the functioning of domestic enterprises and meet the needs of stakeholders in corporate relations.
Keywords: management, corporate governance, corporation, corporate sector